2020
DOI: 10.1111/1440-1703.12125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of source habitat spatial heterogeneity and species diversity on the temporal stability of aquatic‐to‐terrestrial subsidy by emerging aquatic insects

Abstract: Duration and temporal stability of resource subsidy largely affect the response of recipient communities. Factors that influence the temporal dynamics of resource subsidy from aquatic-to-terrestrial habitats by emerging aquatic insects were examined in this study. By measuring the flux of aquatic insect

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Aquatic insect emergence from streams to riparian forests can be important prey subsidies for riparian predators, such as birds, spiders and bats (Baxter, Fausch, & Carl Saunders, 2005). Uno and Pneh (2020) examined the assemblages of aquatic insects that constitute emergence fluxes at different habitats along a temperate river in California. They found that the same species from different habitats emerged at different timing, and different species from the same habitat emerged at different timing.…”
mentioning
confidence: 99%
“…Aquatic insect emergence from streams to riparian forests can be important prey subsidies for riparian predators, such as birds, spiders and bats (Baxter, Fausch, & Carl Saunders, 2005). Uno and Pneh (2020) examined the assemblages of aquatic insects that constitute emergence fluxes at different habitats along a temperate river in California. They found that the same species from different habitats emerged at different timing, and different species from the same habitat emerged at different timing.…”
mentioning
confidence: 99%
“…In the future, aquatic insect assemblage changes due to pesticides may increase because of increasing global pesticide use (Bernhardt et al, 2017; Kattwinkel et al, 2011) and increasing pesticide toxicity towards aquatic insects (Schulz et al, 2021). These trends could lead to higher variability in emergence (Uno & Pneh, 2020), therefore altering foraging opportunities for predators (Armstrong et al, 2016). Further, pesticide toxicity has been shown to cause earlier insect emergence (Cavallaro et al, 2018), which may affect the growth rate, population biomass, and maturity rate of predators (Sato et al, 2016) and may lead to a mismatch in predator and prey cycles.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, emergence timing depends on the composition of aquatic insects because individual species exhibit differences in phenology. Complementary phenology between species contributes to temporal stability of emergence (Uno & Pneh, 2020), improving foraging opportunities for predators (Armstrong et al, 2016).…”
mentioning
confidence: 99%
“…If salmonfly emergence were synchronous across a basin or over long river segments, birds would have only a few days to locate and exploit the salmonflies. However, spatial variation in the phenology of emergence like we observed bracketing major tributary confluences, or that can occur at smaller scales within reaches (e.g., Gregory et al, 2000;Uno, 2016;Uno and Pneh, 2020), may allow mobile consumers to extend their foraging opportunities by foraging sequentially among localized pulses. In fact, our observations likely provide a conservative account of the potential for this phenomenon.…”
Section: Discussionmentioning
confidence: 78%